Aplicação do controle estatístico do processo das análises físicoquímicas de crioscopia e acidez tuteláveis: um estudo de caso em uma oraganização beneficiadora de laticínios do Rio Grande do Norte - Azevedo, Renan Marques de (Universidade Federal Rural do Semi-Árido, 2020)
This work comprises an important segment for the well-being and food of the human being: milk, which is still a widely consumed food, especially at the beginning and end of life. Milk’s consumption is very important for the maintenance of essential nutrients throughout life. For this reason, it is essential that this drink reaches the table of consumers with maximum safety, without risk of contamination or undue alterations. Having this knowledge, this study sheds light on the quality control of pasteurized milk, based on the possibilities of applying quality tools capable of providing reliability in the production process. The study general objective, therefore, is to apply the Statistical Process Control (SPC) tool in the testing of cryoscopy and acidity indicators of milk in a Dairy Processing Organization. Based on the reference standards established by the Institute of Defense and Agricultural Inspection of Rio Grande do Norte (IDAIRN) for the mentioned indicators, the work prepared Letters of Control X and R for analysis of the data provided by the Dairy Organization studied, in order to identify the variability of the physical-chemical analysis process in line with the established legal limits. Analysing the results, it was noticed that the process is out of control in most of the tests, which shows the necessity of elaboration of actions capable of identifying, classifying and controlling which suppliers deliver the raw material within the required specifications.
Monografia
Keywords: Indústria de Laticínios; Controle Estatístico do Processo; Cartas de Controle; Dairy Industry; Statistical Process Control; Control Cards; ENGENHARIAS::ENGENHARIA DE PRODUCAO